Canada GEESE 2. Visualization of Integrated Marine Geoscience Data for Canadian and Proximal Waters - Courtney, Robert (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2013)
SUMMARY The Geological Survey of Canada has made most of its holdings of marine geoscience data available online with unrestricted access. These holdings constitute the premier collections of geological and geophysical source data for Canadian and proximal waters. Multibeam bathymetric imagery, analog high resolution seismic and sidescan sonar data, seabed photographs, grain size analyses, and radiocarbon dates can be directly downloaded from NRCan’s Geogratis (http://geogratis.cgdi.gc.ca) servers. KML files allow the user to discover and explore these collections, highlighting the building blocks of marine data downloadable from ftp/http servers.